'A friendship that will define you both': Star Trek and the devolution of American masculinity. (October 2016) - Kies, Bridget
Abstract : This article compares the shift in the presentation of masculinity in the rebooted Star Trek films to masculinity in the original series and in fan fiction. It argues that, unlike their original counterparts, the rebooted Kirk and Spock exemplify aspects of hegemonic masculinity that are counter to the principles of Star Trek, reflecting post-9/11 reactionary politics. At the same time, however, fan fiction and fan communities celebrate the more liberatory potential of the reboot universe for new sexual identities and sexual expression. This article argues that this swapping of ideology reveals the ways in which Star Trek 's true essence lies not in what it does or does not present but in how it inspires audiences to strive for a utopian future.